2021
DOI: 10.3389/fphys.2021.726434
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Apnea-Induced Hypoxia on Cardiovascular Adaptation and Circulating Biomarkers of Oxidative Stress in Elite Breath-Hold Divers

Abstract: Given the previous evidence that breath-hold diving is a cause of physiological stress, this study aimed to determine whether a combination static and dynamic apnea would affect total oxidant status, nitric oxide, heat shock proteins and cardiovascular parameters in elite freedivers. Thirteen finalists of the World and European championships in swimming pool breath-hold diving participated in the study. Whole-body plethysmography and electrocardiography was performed to determine the cardiorespiratory variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…ROS can also oxidize nitric oxide synthase (NOS) cofactor tetrahydrobiopterin (BH4) into dihydrobiopterin (BH2), which causes a reduced liberation of NO uncoupling endothelial NO synthase [ 51 ], leading to endothelial dysfunctions [ 52 ]. NO can be preserved by the activation of antioxidant defenses, as observed by several authors that found NO increases during the deep phases of both SCUBA and BH dives [ 53 ]. The same tendencies have been shown in SCUBA [ 54 ] or CCR diving [ 55 ].…”
Section: Oxy-inflammation-related Mechanisms and Outcomesmentioning
confidence: 90%
“…ROS can also oxidize nitric oxide synthase (NOS) cofactor tetrahydrobiopterin (BH4) into dihydrobiopterin (BH2), which causes a reduced liberation of NO uncoupling endothelial NO synthase [ 51 ], leading to endothelial dysfunctions [ 52 ]. NO can be preserved by the activation of antioxidant defenses, as observed by several authors that found NO increases during the deep phases of both SCUBA and BH dives [ 53 ]. The same tendencies have been shown in SCUBA [ 54 ] or CCR diving [ 55 ].…”
Section: Oxy-inflammation-related Mechanisms and Outcomesmentioning
confidence: 90%
“…Data related to the NO production and antioxidant synthesis could explain the well-known BH-diving-related vascular adaptation and the response to oxidative stress during diving deep phase, as observed by SCUBA and BH-diving underwater blood draw studies [ 37 , 44 ]. Finally, there are interesting data related to the hypoxia [ 72 , 73 ] stimulus that indirectly may confirm that the muscle apparatus works under strong exposure conditions notwithstanding the very short/low intensity of exercise, due to the intermittent hypoxia caused by repetitive diving.…”
Section: Discussionmentioning
confidence: 99%